Enhanced Antioxidant Gel Formulation with Papaya Leaf Extract and Virgin Coconut Oil: Optimization Approach - Sukamdi, Dyani Primasari; Ileina, Sophia Farra; Erviana, Rima; Damarwati, Vella Lailli; Harimurti, Sabtanti; Amid, Azura (Borneo Journal of Pharmacy, 2026)
Redness, pigmentation, premature aging, xerosis, and even the risk of cancer can result from excessive exposure to free radicals in the form of ultraviolet (UV) radiation, which can cause skin damage. Antioxidants, including β-carotene, α-tocopherol, ascorbic acid, and flavonoids, are present in papaya (Carica papaya) leaves and Virgin Coconut Oil (VCO). Therefore, these two components may mitigate skin imperfections caused by premature aging. This study aims to formulate and determine the antioxidant activity contained in C. papaya leaf extract gel and VCO. A laboratory-based experimental approach was implemented in this study. Using the infusion method, C. papaya leaves were extracted for 15 minutes to initiate the gel formation. The C. papaya leaf extract gel with VCO was divided into five formulations, with varying amounts of each ingredient. Organoleptic, homogeneity, viscosity, pH, spreadability, and antioxidant activity tests, conducted using the DPPH method, are included in the preparation testing process. The antioxidant activity test of C. papaya leaf extract gel with VCO in each formula yielded values of 91.32 ppm, 121.21 ppm, 80.19 ppm, 67.04 ppm, and 55.31 ppm, respectively. The results indicated that the quality of the gel preparation and the IC50 value of the C. papaya leaf extract gel were influenced by variations in VCO concentration.